OPTIMIZED METHOD FOR DNA EXTRACTION AND PCR AMPLIFICATION IN AROEIRA TREE - Silva, Jailson Do Nascimento; Linhares, Amanda Camila Dos Santos; Palmieri, Dario Abel [UNESP]; Costa, Marcones Ferreira; de SÁ, Gisele Holanda; Gomes, Maria Fernanda da Costa; Dos Santos, Michelli Ferreira; Feitoza, Lidiane de Lima; Valente, Sérgio Emílio Dos Santos (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2023)
Molecular markers are important tools in the characterization of plant genetic diversity and can provide support for conservation strategies for endangered populations. The different molecular techniques involve the evaluation of many individuals; therefore, it is crucial to have fast, efficient, and inexpensive methods for DNA extraction. Given the importance of the Aroeira (Myracrodruon urundeuva Fr. All.) it is pertinent to optimize a protocol that allows the obtainment of intact and pure DNA, aiming to assist conservation strategies for this species that is threatened with extinction. Thus, this study aimed to compare five DNA extraction methods: Dellaporta et al. (1983), Doyle and Doyle (1987) modified, Ferreira and Grattapaglia (1995), Romano and Brasileiro (2015), and Khanuja et al. (1999) and optimize the most efficient protocol for M. urundeuva. The modified DNA extraction protocol proposed by Doyle and Doyle (1987), using 100 mg of leaf tissue and 6 µl of β-mercaptoethanol was the protocol that presented the sharpest bands after DNA electrophoresis and after the reactions of amplification employing Polymerase Chain Reaction (PCR). Therefore, it is suggested to use the protocol described by Doyle and Doyle (1987) modified for the extraction of DNA from young M. urundeuva leaves to carry out techniques involving molecular markers.
Keywords: CTAB; DNA isolation; Myracrodruon urundeuva